A critical review of the impacts of cover crops on nitrogen leaching, net greenhouse gas balance and crop productivity. (13th May 2019) - Abdalla, Mohamed; Hastings, Astley; Cheng, Kun; Yue, Qian; Chadwick, Dave; Espenberg, Mikk; Truu, Jaak; Rees, Robert M.; Smith, Pete
Abstract: Cover crops play an increasingly important role in improving soil quality, reducing agricultural inputs and improving environmental sustainability. The main objectives of this critical global review and systematic analysis were to assess cover crop practices in the context of their impacts on nitrogen leaching, net greenhouse gas balances (NGHGB) and crop productivity. Only studies that investigated the impacts of cover crops and measured one or a combination of nitrogen leaching, soil organic carbon (SOC), nitrous oxide (N2 O), grain yield and nitrogen in grain of primary crop, and had a control treatment were included in the analysis. Long‐term studies were uncommon, with most data coming from studies lasting 2–3 years. The literature search resulted in 106 studies carried out at 372 sites and covering different countries, climatic zones and management. Our analysis demonstrates that cover crops significantly ( p < 0.001) decreased N leaching and significantly ( p < 0.001) increased SOC sequestration without having significant ( p > 0.05) effects on direct N2 O emissions. Cover crops could mitigate the NGHGB by 2.06 ± 2.10 Mg CO2 ‐eq ha −1 year −1 . One of the potential disadvantages of cover crops identified was the reduction in grain yield of the primary crop by ≈4%, compared to the control treatment. This drawback could be avoided by selecting mixed cover crops with a range of legumes and non‐legumes, which increased the yield by ≈13%. These advantages of cover crops justify their widespread adoption. However, management practices in relation to cover crops will need to be adapted to specific soil, management and regional climatic conditions. Abstract : Cover crops significantly ( p < 0.001) decreased N leaching and significantly ( p < 0.001) increased soil organic carbon sequestration without having significant ( p > 0.05) effects on direct N2 O emissions. Cover crops could mitigate net greenhouse gas balance by 2.06 ± 2.10 Mg CO2 ‐eq ha −1 year −1 . One of the potential disadvantages of the cover crops identified was the reduction in grain yield of the primary crop by ≈4%, compared to the control treatment. This drawback could be avoided by selecting legume–non‐legume mixed cover crops. However, cover crop management need to be adapted to specific soil, management and regional climatic conditions.